2015
DOI: 10.3109/10428194.2015.1092528
|View full text |Cite
|
Sign up to set email alerts
|

Pri-miR-34b/c rs4938723 polymorphism contributes to acute lymphoblastic leukemia susceptibility in Chinese children

Abstract: A polymorphism rs4938723 (T > C) within the promoter region of pri-miR-34b/c has been found to not only affect the expression of mature miR-34b/c but also contribute to the susceptibility to several cancer types. We designed a case-control study to evaluate the role of rs4938723 in childhood acute lymphoblastic leukemia (ALL). The rs4938723 CC genotype was significantly associated with reduced ALL risk (p = 0.003, ORadjusted = 0.51, 95% CI = 0.33-0.80 for CC vs. TT). Stratification analyses showed the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…The rs4938723 polymorphism has been shown to influence the cell cycle of downstream cells, as well as induce changes in the expression of key genes in the apoptotic pathway, thereby influencing cancer susceptibility. Several studies have reported a significant association between the rs4938723 polymorphism and risk of malignant tumors such as acute lymphoblastic leukemia, cervical cancer, papillary thyroid carcinoma, gastric cancer, esophageal squamous cell carcinoma, renal cell cancer, and colorectal cancer (Oh et al, 2014;Zhang et al, 2014a,b;Chen et al, 2015;Pan et al, 2015;Tong et al, 2016;Yuan et al, 2016). A previous large-scale case-control study comprising 1109 esophageal squamous cell carcinoma patients and 1275 healthy subjects reported a correlation between the GG genotype of miR-34b/c and a significantly reduced risk of esophageal squamous cell carcinoma in a Chinese population (Zhang et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…The rs4938723 polymorphism has been shown to influence the cell cycle of downstream cells, as well as induce changes in the expression of key genes in the apoptotic pathway, thereby influencing cancer susceptibility. Several studies have reported a significant association between the rs4938723 polymorphism and risk of malignant tumors such as acute lymphoblastic leukemia, cervical cancer, papillary thyroid carcinoma, gastric cancer, esophageal squamous cell carcinoma, renal cell cancer, and colorectal cancer (Oh et al, 2014;Zhang et al, 2014a,b;Chen et al, 2015;Pan et al, 2015;Tong et al, 2016;Yuan et al, 2016). A previous large-scale case-control study comprising 1109 esophageal squamous cell carcinoma patients and 1275 healthy subjects reported a correlation between the GG genotype of miR-34b/c and a significantly reduced risk of esophageal squamous cell carcinoma in a Chinese population (Zhang et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis performed by Wang et al (38) suggests that the pri-miR-34b/c rs4938723 polymorphism may be associated with the risk of cancer, including nasopharyngeal cancer, osteosarcoma and renal cell cancer. Tong et al (39) reported that the rs4938723 variant significantly decreased the risk of Chinese childhood acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Other scholars suggested that miR-27a rs895819 polymorphism could affect the expression of its targeted gene ZBTB1038. And the promoter polymorphism of miR-34b/c rs4938723 could influence the transcription activity of miR-34b/c promoter, which therefore affect miRNA expression3940. As the three described polymorphisms of let-7e, miR-4795 and miR-365b are all located in the important promoter regions, we speculate that these miRNA SNPs may be associated with the downregulation of PGC expression, thus increasing gastric cancer risk.…”
Section: Discussionmentioning
confidence: 99%